(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Adolescents are a vulnerable group for developing unhealthy eating habits, especially with the increasing availability of junk food in the market. Private schools, which often provide a comfortable environment and higher income families, may also have an impact on the eating behavior of adolescents. Therefore, this cross-sectional study aimed to investigate the knowledge and behavior related to junk food among adolescent students in a private school. MATERIALS AND METHODS: A cross-sectional descriptive study was conducted among adolescent students in Shree Phuleshwar Public Secondary English school Kalyanpur, Saptari with the sample drawn from those present during data collection. Following their consent, the respondents were given a self-administered structured questionnaire. Knowledge was graded; mean, standard deviation, frequency, percentage and the chi-square test were used to analyze the data using SPSS 16.0. RESULTS: The participants’ mean knowledge score was 5.80, with a standard deviation of 1.26. Similarly, the participants’ average practice score was 7.07, with a standard deviation of 1.20.A total of 60 people took part in the study. The findings revealed that 31.7% of the participants possessed good knowledge, 31.7% possessed average knowledge, and 36.7% possessed poor knowledge. In terms of practice, 35.0% of participants did well, while 65.0% did poorly. CONCLUSIONS: The level of knowledge among adolescent students in Kalyanpur school was generally low, with only a small proportion having good knowledge. Similarly, the level of practice was poor, with the majority of participants having poor practice.